Modeling large deformation and failure of expanded polystyrene crushable foam using LS-DYNA - Shah, Qasim Hussain; Topa, Ameen (Hindawi Publishing Corporation, 2014)
In the initial phase of the research work quasi-static compression tests were conducted on the expanded polystyrene (EPS) crushable foam for material characterisation at low strain rates (8.3x10-3~8.3x10-2 s-1) to obtain the stress strain curves. The resulting stress strain curves compared well with the ones found in the literature. Numerical analysis of compression tests were carried out to validate them against experimental results. Additionally gravity-driven drop tests were carried out using a long rod projectile with semi-spherical end that penetrated into the EPS foam block. Long rod projectile drop tests were simulated in LS-DYNA by using suggested parameter enhancements that were able to compute the material damage and failure response precisely. The material parameters adjustment for a successful modelling has been reported.